Smart Home Energy Management System Based On Demand Response Management - Dhinakar, P.; Sunder, A.John Clement; Ramesh, S.M.; Kirubaharan, D.Vignesh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In this paper we present a home energy management system with energy demand management. The proposed system will have control of different appliances that are available in the home. It manages household loads according to their predefined priority and guarantees the total household power consumption below certain levels. The home energy management system will receive the demand response from the utility side. The goal of the system is to encourage the consumer to use less energy during peak hours or to move the time of energy use to off peak times such as nighttime and weekends. Thus the high peak-to-average ratio (PAR) of power will be avoided and also we adopt real time pricing. The utility company use real time dynamic pricing to coordinate demand responses to the benefit of the overall system.